Refocussing Mathematics and Science Education towards Addressing Security Challenges for National Development in Nigeria - OGUNDELE, Anthony Taiwo; AZAGBAEKWUE, Anthony; AROWOLO, Jacob Gbemiga (Ilorin Journal of Education, 2024)
This paper addresses the need to refocus mathematics and science education towards eradicating security challenges for national development. The value of mathematics is felt in the areas of science discoveries and inventions. Science and Mathematics education is considered as a tool to helping people create a society characterized by dignity for all, and in which injustice, arrogance, violence and bigotry have no place in the society. The need to refocus mathematics and science education becomes imperative because knowledge expands people’s possibilities, promote creativity and imagination and the products of science and mathematics engage problems as wide ranging as cryptography, budgetary, financial, capital index, income index, education index and consumer price record. Likewise, it harnesses how mathematics and science education can address the challenges of national security to restore peace in Nigeria. It was recommended among others that graduate of mathematics and science education should be made to acquire practical skills that will enable them to be self-employed in the future and that government should be more proactive in responding to the acts and emergent security threat in the country.